2019
DOI: 10.1055/s-0039-1677737
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perceptions of the Electronic Problem List in Pediatric Trauma Care

Abstract: Objective To describe physician perceptions of the potential goals, characteristics, and content of the electronic problem list (PL) in pediatric trauma. Methods We conducted 12 semistructured interviews with physicians involved in the pediatric trauma care process, including residents, fellows, and attendings from four services: emergency medicine, surgery, anesthesia, and pediatric critical care. Using qualitative content analysis, we identified PL goals, characteristics, and patient-related info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Lacking content and poor presentation has also been reported by previous studies that examined factors influencing problem list use. 5,7,8,10,21,34,35 These studies also support our findings with regard to the lack of policies and guidelines 5,35 and lack of training. 5,21,34 In our study, we further identified how training can be improved: by involving "champions" in small peer groups.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Lacking content and poor presentation has also been reported by previous studies that examined factors influencing problem list use. 5,7,8,10,21,34,35 These studies also support our findings with regard to the lack of policies and guidelines 5,35 and lack of training. 5,21,34 In our study, we further identified how training can be improved: by involving "champions" in small peer groups.…”
Section: Discussionsupporting
confidence: 77%
“…[2][3][4] Accurate problem lists that provide a concise summary of patient problems can therefore help physicians to track a patient's status and progress, and organize clinical reasoning and documentation. 3,5,6 Although physicians and patients acknowledge the value of an accurate problem list, 7,8 problem lists often remain incomplete, due to lack of responsibility, incomplete and inaccurate content of the underlying terminology, and because of little technical and administrative support. 5,9,10 Subsequently, physicians often modify these coded problems to their preferences, by adding details for these problems in clinical notes.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to documentation support, clinicians' EHR use is also known to aid in achieving other important goals, such as communicating with team members and synthesizing large amounts of information. 7 However, literature suggests that the introduction of EHRs has not always considered the nature of work in the ED, resulting in transformed and suboptimal workflow leading to substantial frustrations with the systems. 8,9 In the United States, studies investigating the impact of EHRs on clinical workflows suggest that the docu-mentation has increased over the last decade, with 50 to 65% time spent on EHR-related activities.…”
Section: Background and Significancementioning
confidence: 99%
“…This focus on reducing the unintentional negative effects of electronic health records (EHRs) is important as EHRs are becoming increasingly linked to physician dissatisfaction and burnout. [7][8][9][10][11] Over the past 15 years, attempts have been made to create a standardized method of recording CCs. 12 Prior attempts have failed to gain widespread acceptance for various reasons: they may not be freely sharable or may not have had the right level of specificity, structure, and clinical relevance to gain acceptance by the larger emergency medicine community.…”
Section: Background and Significancementioning
confidence: 99%